Identification of c-MYC SUMOylation by Mass Spectrometry - Kalkat, Manpreet (PLoS One, 2014)
The c-MYC transcription factor is a master regulator of many cellular processes and deregulation of this oncogene has been linked to more than 50% of all cancers. This deregulation can take many forms, including altered post-translational regulation. Here, using immunoprecipitation combined with mass spectrometry, we identified a MYC SUMOylation site (K326). Abrogation of signaling through this residue by substitution with arginine (K326R) has no obvious effects on MYC half-life, intracellular localization, transcriptional targets, nor on the biological effects of MYC overexpression in two different cell systems assessed for soft agar colony formation, proliferation, and apoptosis. While we have definitively demonstrated that MYC SUMOylation can occur on K326, future work will be needed to elucidate the mechanisms and biological significance of MYC regulation by SUMOylation.